The Effect of Coordination and Employee Spirit on Employee Work Productivity at The Indonesian National Army Health Education Center Army - Sepudin Sepudin; Yuni Pratikno; Sitta Kusuma (Dinasti International Journal of Management Science, 2026)
The aim of this study is the influence of individual characteristics on work productivity, the influence of work enthusiasm on employee work productivity and to determine the influence of coordination and work enthusiasm simultaneously on employee work productivity at the Indonesian Army Health Education Center. The calculated t value for Coordination (X1) is 5.726, the ttable value for N = 50 is 2.009. So 5.726 > 2.009, then H0 is rejected and Ha is accepted, that Coordination (X1) has a significant effect on Work Productivity (Y), the calculated tvalue Work enthusiasm (X2) is 7.761, the ttable value for N = 50 is 2.009. So 7.761 > 2.009, then H0 is rejected and Ha is accepted, it can be partially that Work enthusiasm (X2) has an effect on Work Productivity (Y). test ANOVA is 317,608 While F table (a0.05) for N = 50 is 2.79. So Fcount > from Ftable (a0.05) or 317,608 > 2.79 that Coordination (X1) and Work Spirit (X2) together influence Work Productivity (Y). Adjusted R Square (R2) value is 0.931. This shows that 93.1% of Coordination (X1) and Work Spirit (X2) simultaneously influence Employee Work Productivity (Y) while the remaining 6.9% is influenced by other factors not studied.